Content Analysis of an EAP Coursebook in an Islamic University - Agus Husein As Sabiq; Muflihah Muflihah (English Education Department at FKIP Nommensen University, 2021)
Evaluating a coursebook is necessary to find the strengths and weaknesses to improve the quality of sources and professional development. This study aimed to investigate the suitability of EAP coursebook materials with the criteria for good teaching materials and the English language needs of IAIN Purwokerto students. The study engaged 83 second-semester students at IAIN Purwokerto, who were randomly drawn from each study program at IAIN Purwokerto. The researchers employed a content analysis procedure: the unit of analysis covering places, actors, activities, research variables in the form of teaching materials in EAP courses, and data collection using a checklist. The analysis of the research is based on the criteria of good teaching materials and the students' English needs which cover the target requirement component for needs analysis, consisting of the students’ needs, shortcomings, and desires. The researchers found that the suitability of the coursebook with the criteria for good text teaching materials has average level of relevance of 50.13%, which is quite appropriate in the category. There were some weaknesses or shortcomings that made this EAP course book not classified as a high level of relevance. English language needs of IAIN Purwokerto students tend to learn integrated language skills, especially speaking and listening.